Arktická expedice na souostroví Svalbard pokračuje - Elster, J. (Josef); Klimešová, J. (Jitka); Ditrich, O. (Oleg) (2010)
Research phycology-microbiology, plant ecology, parasitology- zoology and climatology to Svalbard.